Incorporação de nanopartículas de prata em de vidros teluritos dopados com Pr3+ - Taniguchi, Maiara Mitiko (2018)
In order to improve the efficiency of optical devices, researchers have investigated the effects of the incorporation of metallic nanoparticles into materials containing rare earth. In this work, the effects of AgNO3 variation on doped telurite glass with 0.1 mol% of Pr3+ produced by the melting-quenching method were studied. The samples were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Differential scanning calorimetry (DSC), absorption and luminescence spectroscopy, lifetime and index refraction. The XRD curves demonstrated the non-crystalline nature of the samples whereas the FTIR spectra showed that the vibrational groups did not change after silver addition. By means of the DSC curves an increase of approximately 70 °C in the thermal stability of the TWNN glasses with the addition of silver was verified. From the absorption spectra in the visible region it was possible to verify the surface plasmon resonance band (SPR) centered at 500 nm. The luminescence measurements, in the other hand, showed an increase and quenching in the intensities of the bands coming from the electronic transitions of Pr3+. It was observed that the band between 480-520 nm presents quenching, this is possibly due to the proximity of the SPR band. The bands between 575-675 nm, in turn, had an improvement in the intensity of the luminescences due to the incorporation of AgNPs evidencing that the addition of AgNO3 provides improvements in the intensity of some electronic transitions of the Pr3+ ion. Future works involving complementary measures will be performed as well as the use of other rare earth ions in the TWNN matrix.